Estrategias lúdicas en la enseñanza-aprendizaje de la suma y resta en los estudiantes del nivel elemental de la escuela “Buenos Aires” - Saraguro Díaz, Rosa Elvira (2022)
The present research work encompasses the problem of the difficulty that infants have in basic operations such as addition and subtraction; starting from the premise that play strategies directly influence the optimal development of learning; the lack of them limits the acquisition of knowledge, demotivates the individual, which influences their development, encouraging memorization and repetition. Given this reality, with the purpose of improving the quality of education, and knowing that the game motivates and leads to clear doubts and appropriate knowledge based on support material that generates significant learning, the main objective of this study was to analyze the impact of addition and subtraction play strategies applied in the teaching-learning process in elementary level students of the "Buenos Aires" school in the Paltas canton during the 2021-2022 school year. The approach used was quantitative with a descriptive design, with the participation of 31 students corresponding to the second, third and fourth grade of basic education; inductive-deductive, analytical, synthetic, descriptive, and ethical methods were used, and a questionnaire consisting of 10 questions was applied as an instrument. The results obtained showed that there is a deficient application of playfulness during the teaching-learning process of addition and subtraction. It is concluded that there are weaknesses in the inclusion of playful strategies in the process of teaching addition and subtraction; rather, they are dedicated to imparting only theory, obviating the use of tools that contribute to the effective performance of the contents. Key words: Playful estrategies, teaching learning, meaningful learning